The Effectiveness of Using the Aural-Oral Approach in Arabic Learning (Mufradāt) - Nisa, Andini Zahrotun; Sopian, Asep; Nurbayan, Yayan (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Learning Arabic vocabulary (mufradāt) often faces challenges in achieving effectiveness, particularly in motivating students to actively participate and deeply understand the material. Many conventional methods have significantly failed to improve students' listening and speaking skills. This study aims to analyze the effectiveness of using the Aural-Oral Approach in teaching Arabic vocabulary (mufradāt). The Aural-Oral Approach, which emphasizes intensive listening and speaking skills, can enhance students' vocabulary acquisition in Arabic. This study was conducted at Madrasah Diniyah Takmiliyah (MDT) Ar-Rahman Bogor using a quantitative approach with a quasi-experimental design. The research sample consisted of 60 students divided into two groups: the experimental group using the Aural-Oral Approach and the control group using conventional methods. Data were collected through interviews and vocabulary tests before and after the intervention. The results of the data analysis showed a significant increase in Arabic vocabulary skills in the experimental group compared to the control group. This study's novelty lies in applying the Aural-Oral Approach in the context of Arabic language learning at the MDT level, which has not been extensively explored before. These findings indicate that the Aural-Oral Approach effectively improves Arabic vocabulary mastery. Therefore, it is recommended that this method be more widely implemented in Arabic language teaching to maximize student learning outcomes.